Prevalence of depressive symptomatology among nursing students during the COVID-19 pandemic - Santangelo, O. E.; Provenzano, S.; Armetta, F.; Pesco, G.; Allegro, A.; Lampasona, M.; Pantaleo, L.; Terranova, A.; D'Anna, G.; Firenze, A. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. COVID-19 and the policies to contain it have been a social problem and public health emergency for people in Italy in 2020. The aim of the study is assessing the prevalence of depression symptoms among nursing students from the University of Palermo during the COVID-19 pandemic. Materials and methods. The study employed a cross-sectional study design. On April 2020, a survey was performed including all the nursing students of the University of Palermo. The survey was structured into two parts. The first part consisted in the collection of socio-demographic information, the second in the administration of the QIDS-SR16 questionnaire. A multivariable logistic regression model was used to elaborate the results and adjusted Odds Ratios are presented. Results. The sample consisted of 525 students (70.3% female). The probability to have a moderate/severe/ very severe depressive symptomatology is significantly associated with the following variables: “Female gender” (aOR 1.96), “Low perceived economic status” (aOR 2.32), “Low perceived health status” (aOR 2.30) and “To be a smoker” (aOR 2.24). Conclusions. The global pandemic and the efforts to contain it represent a unique event and offer the opportunity to advance our understanding of how to provide mental health care focused on online psychoeducation and psychotherapy programs for young students.